(untitled) (Research, Society and Development, 2021)
Objectives:To investigate the benefits of dual task training in the treatment of Parkinson’s disease.Methods: This is an integrative review, where 03 papers were used to compose this work. The database used was Google Scholar, with papers published in the last 10 years, and researched papers in English and Portuguese. Results: the study allowed the analysis of the elderly with PD, as to the performance of motor activities of dual task, the group with Parkinson’s disease showed improvement in the development of tasks taking into account the time and difficulty of the exercise proposed, while the group of elderly who do not have PD the time and difficulty of the activity proposed was considered lower. Conclusion: From the conclusion of this study we observed the importance of dual task activities for people with Parkinson’s disease, because they are simple activities that are effective in the developed activities, with the aim of stimulating speech, movement, muscle stiffness, gait training and others.